Penentuan Jadwal Overtime Dengan Klasifikasi Data Karyawan Menggunakan Algoritma C4.5 - Romli, Ikhsan; Zy, Ahmad Turmudi (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Technological development and scientific advancement are very important and influential parts of all fields. With the development and advancement of technology, being experts in a field is a must because it is required to know more and learn about the technology that is currently developing. Information technology and informatics are needed to support performance. Large and small companies also need fast and accurate information to make easier decisions making. Therefore, data mining classification techniques are needed to solve these problems. The classification used in data mining is a Decision tree because it is a technique that is widely used and produces output with existing rules so that it can present employee data to determine the overtime schedule. This study uses the C4.5 algorithm to determine the overtime schedule. The test results of the overtime schedule with the C4.5 algorithm with the Confusion matrix have good accuracy, precision, and recall values, namely 91% accuracy, 86.05% precision, and 92.5% recall.